Chapter Review on Functions and Transformation and Inverse
Chapter
Chapter 2
Section
Chapter Review on Functions and Transformation and Inverse
You need to sign up or log in to purchase.
You need to sign up or log in to purchase.
Solutions 55 Videos

Determine if the functions in each pair are equivalent.

f(x) = -4(x^2 + x - 2) + (2x - 3)^2, g(x) = x^2 - 16x + 17

Buy to View
Q1a

Determine if the functions in each pair are equivalent.

f(x) = 5(x ^2 + 2x - 3) - (2x + 5)(-x + 1), g(x) = 7x^2 + 13x - 20

Buy to View
Q1b

Determine if the functions in each pair are equivalent.

f(x) = (x + 5)^2 - 2(3 - x)(x + 1), g(x) = -2(-x^2 + 4x - 8) + (x + 4)^2 - 6

Buy to View
Q1c

State the restrictions on f(x). Then determine whether g(x) is the simplified version of f(x). If not, determine the proper simplified version.

f(x) = \dfrac{8x^2 + 10x - 3}{4x^2 - x}

g(x) = \dfrac{2x + 3}{x}

Buy to View
Q2a

State the restrictions on f(x). Then determine whether g(x) is the simplified version of f(x). If not, determine the proper simplified version.

f(x) = \dfrac{8x^2 - 12x - 8}{4x^2 - 8x}

g(x) = 2x + 1

Buy to View
Q2b

Simplify each expression and state any restrictions on x.

\dfrac{x + 8}{x^2 + 10x + 16}

Buy to View
Q3a

Simplify each expression and state any restrictions on x.

\dfrac{8x^2 - 6x - 9}{4x^2 + 27x + 18}

Buy to View
Q3b

Simplify and state any restrictions.

\dfrac{64a^2b}{21ab^2} \times \dfrac{63a^3b^3}{8a^2b}

Buy to View
Q4a

Simplify and state any restrictions.

\dfrac{54a^3b^2}{81c^2} \div \dfrac{108a^2b}{45c}

Buy to View
Q4b

Simplify and state any restrictions.

\dfrac{3x - 4}{x + 9} \times \dfrac{2x + 18}{3x - 4}

Buy to View
Q4c

Simplify and state any restrictions.

\dfrac{x^2 - 5x - 24}{x^2 - 2x - 15} \times \dfrac{x - 5}{x + 4}

Buy to View
Q4d

Simplify and state any restrictions.

\dfrac{x - 4}{x - 3} \div \dfrac{4 - x}{2x - 6}

Buy to View
Q4e

Simplify and state any restrictions.

\dfrac{x^2 + 11 x + 24}{x^2 + 2x - 3} \div \dfrac{x - 8}{x - 1}

Buy to View
Q4f

Simplify and state any restrictions.

\dfrac{2}{3x} + \dfrac{3}{5x}

Buy to View
Q5a

Simplify and state any restrictions.

\dfrac{2 - a}{6ab} + \dfrac{7 + b}{12b^2}

Buy to View
Q5b

Simplify and state any restrictions.

\dfrac{x + 10}{x - 1} + \dfrac{x - 3}{x + 2}

Buy to View
Q5c

Simplify and state any restrictions.

\dfrac{8x - 3}{x^2 - 7x + 12} - \dfrac{2x + 1}{x - 4}

Buy to View
Q5d

Simplify and state any restrictions.

\dfrac{4x + 1}{x + 3} + \dfrac{x - 6}{x^2 - 9}

Buy to View
Q5e

Simplify and state any restrictions.

\dfrac{5x + 25}{x^2 + 7x + 10} + \dfrac{10x - 20}{x^2 - 4}

Buy to View
Q5f

Use the base function f(x) = x. Write the equation for each transformed function.

s(x) = f(x + 2) - 8

Buy to View
Q6a

Use the base function f(x) = x. Write the equation for each transformed function.

(x) = f(x - 5) + 1

Buy to View
Q6b

Repeat question 6 for each base function.

f(x) = x^2

Buy to View
Q7i

Repeat question 6 for each base function.

f(x) = \sqrt x

Buy to View
Q7ii

Repeat question 6 for each base function.

f(x) = \dfrac{1}{x}

Buy to View
Q7iii

Each graph represents a transformation of one of the base functions f(x) = x, f(x) = x^2, f(x) = \sqrt x, or f(x) = \dfrac{1}{x}. State the base function and the equation of the transformed function. Buy to View
Q8a

Each graph represents a transformation of one of the base functions f(x) = x, f(x) = x^2, f(x) = \sqrt x, or f(x) = \dfrac{1}{x}. State the base function and the equation of the transformed function. Buy to View
Q8b

Determine if g(x) is a reflection of f(x). Justify your answer.

f(x) = \sqrt {x - 13} + 6

g(x) = -\sqrt {13 - x} - 6

Buy to View
Q9a

Determine if g(x) is a reflection of f(x). Justify your answer.

f(x) = x^2 - 2

g(x) = x^2 - 2

Buy to View
Q9b

Determine if g(x) is a reflection of f(x). Justify your answer.

f(x) = \sqrt {x + 7}

g(x) = \sqrt {x - 7}

Buy to View
Q9c

Determine if g(x) is a reflection of f(x). Justify your answer.

f(x) = \dfrac{1}{x + 15} - 8

f(x) = -\dfrac{1}{x + 15} + 8

Buy to View
Q9d

For each function f(x), determine the equation for g(x).

f(x) = \sqrt {x - 1} + 8

g(x) = -f(x)

Buy to View
Q10a

For each function f(x), determine the equation for g(x).

f(x) = (x - 3)^2 + 10

g(x) = -f(-x)

Buy to View
Q10b

For each function f(x), determine the equation for g(x).

f(x) = \dfrac{1}{x + 7} - 2

g(x) = -f(-x)

Buy to View
Q10c

For each function g(x), identify the value of a or k and describe how the graph of g(x) can be obtained from the graph of f(x).

g(x) = 9f(x)

Buy to View
Q11a

For each function g(x), identify the value of a or k and describe how the graph of g(x) can be obtained from the graph of f(x).

g(x) = f(3x)

Buy to View
Q11b

For each function g(x), identify the value of a or k and describe how the graph of g(x) can be obtained from the graph of f(x).

g(x) = \dfrac{2}{5} f(x)

Buy to View
Q11c

For each function g(x), identify the value of a or k and describe how the graph of g(x) can be obtained from the graph of f(x).

g(x) = f(\dfrac{1}{7} x)

Buy to View
Q11d

For each function g(x), describe the transformation from a base function of f(x) = x, f(x) = x^2, f(x) = \sqrt x, or f(x) = \dfrac{1}{x}. Then transform the graph of f(x) to sketch a graph of g(x).

g(x) = 13x

Buy to View
Q12a

For each function g(x), describe the transformation from a base function of f(x) = x, f(x) = x^2, f(x) = \sqrt x, or f(x) = \dfrac{1}{x}. Then transform the graph of f(x) to sketch a graph of g(x).

g(x) = (5x)^2

Buy to View
Q12b

For each function g(x), describe the transformation from a base function of f(x) = x, f(x) = x^2, f(x) = \sqrt x, or f(x) = \dfrac{1}{x}. Then transform the graph of f(x) to sketch a graph of g(x).

g(x) = \sqrt {\dfrac{x}{3}}

Buy to View
Q12c

For each function g(x), describe the transformation from a base function of f(x) = x, f(x) = x^2, f(x) = \sqrt x, or f(x) = \dfrac{1}{x}. Then transform the graph of f(x) to sketch a graph of g(x).

g(x) = \dfrac{6}{x}

Buy to View
Q12d

Compare the transformed equation to y = af[k(x - d)] + c to determine the values of the parameters a, k, d, and c. Then describe, in the appropriate order, the transformations that must be applied to a base function f(x) to obtain the transformed function.

g(x) = 7f(x -1)

Buy to View
Q13a

Compare the transformed equation to y = af[k(x - d)] + c to determine the values of the parameters a, k, d, and c. Then describe, in the appropriate order, the transformations that must be applied to a base function f(x) to obtain the transformed function.

g(x) = \dfrac{1}{5} f(x) - 3

Buy to View
Q13b

Compare the transformed equation to y = af[k(x - d)] + c to determine the values of the parameters a, k, d, and c. Then describe, in the appropriate order, the transformations that must be applied to a base function f(x) to obtain the transformed function.

g(x) = f(x + 9) + 8

Buy to View
Q13c

Compare the transformed equation to y = af[k(x - d)] + c to determine the values of the parameters a, k, d, and c. Then describe, in the appropriate order, the transformations that must be applied to a base function f(x) to obtain the transformed function.

g(x) = f(\dfrac{1}{2}x) + 10

Buy to View
Q13d

Given each base function f(x), write the equation of the transformed function g(x). Then transform the graph of f(x) to sketch a graph of g(x).

f(x) = \sqrt x

g(x) = 3f(2x)

Buy to View
Q14a

Given each base function f(x), write the equation of the transformed function g(x). Then transform the graph of f(x) to sketch a graph of g(x).

f(x) = \dfrac{1}{x}

g(x) = f(x - 4) + 9

Buy to View
Q14b

Given each base function f(x), write the equation of the transformed function g(x). Then transform the graph of f(x) to sketch a graph of g(x).

f(x) = x^2

g(x) = f[\dfrac{1}{4}(x + 5)]

Buy to View
Q14c

Given each base function f(x), write the equation of the transformed function g(x). Then transform the graph of f(x) to sketch a graph of g(x).

f(x) = x

g(x) = -2f(x - 7)

Buy to View
Q14d

Copy each graph of f(x). Then sketch the inverse of each function, and state the domain and range of the function and of its inverse. Buy to View
Q15a

Copy each graph of f(x). Then sketch the inverse of each function, and state the domain and range of the function and of its inverse. Buy to View
Q15b

Determine an equation for the inverse of each function.

f(x) = -2x + 7

Buy to View
Q16a

Determine an equation for the inverse of each function.

f(x) = \dfrac{5x - 3}{4}

Buy to View
Q16b

Determine an equation for the inverse of each function.

f(x) = (x - 3)^2 + 1

Buy to View
Q16c

Determine an equation for the inverse of each function.

f(x) = -\dfrac{1}{4} x^2 + 9

Buy to View
Q16d